The religious right in the United States: The base of the Bush-Administration? - Josef M. Braml (Stiftung Wissenschaft und Politik (SWP), 2004)
Religious and moral attitudes will be a key factor in the Congressional and Presidential elections on November 2. Does the Religious Right succeed in translating its electoral clout into political representation and policy-making? Does this yield an impact on Washington's foreign policy positions and, particularly, the transatlantic relationship? This study has five main conclusions: 1. The political awakening of conservative Evangelicals and fundamentalist religious movements since the early 1980s is one of the most important cultural changes in the U.S. as it establishes new political structures that influence domestic and foreign policy-making. 2. The Christian Right's voters and interest groups (Political Action Committees, grassroots organizations and think tanks) not only have an impact on elections, but also influence the policy agenda of the U.S. In terms of foreign policy, "true believers" are advocates for America's military might and its unconditional protection of Israel. 3. National security issues and the fight against terrorism play a central role for another reason: They may strengthen the cohesion of a heterogeneous electoral coalition and, thus, help to establish permanent Republican control over Congress and the White House. 4. The religious/moral engagement of the Christian Right is polarizing the United States and has caused and will continue to cause some ruptures in the transatlantic relationship: not only when deliberating about whether to use military force or diplomatic means, but also when taking concrete steps to deal with conflicts, especially in the Middle East. (SWP-Research Papers / SWP)
Keywords: 320